2020
DOI: 10.1177/0306624x20975162
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for an Incarcerated Informed Lens in Therapy

Abstract: Exceptionally high rates of incarceration in the United States have caused a need for a major social justice movement. This paper explains the various collateral damages endured by the incarcerated population. Several research studies related to the unintended consequences of incarceration on outcomes related to couple and family relationships, racial disparities, employment, poverty and public health are examined. The importance of individual, couple, and family therapy and its effectiveness toward improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 77 publications
0
10
1
Order By: Relevance
“…Understanding and recognizing barriers to equal educational experiences for all children can lead to viable solutions related to the effects of incarceration on children (Turney & Haskins, 2014). While we did not find any relationship between coparents who can rely on one another and child outcomes, previous research has shown that children of an incarcerated parent are more likely to experience homelessness, housing instability, food insecurity, and lower rates of educational achievement (Sexton, 2016), thus displaying that this is a systemic problem (Tadros et al, 2021b).…”
Section: Discussioncontrasting
confidence: 96%
“…Understanding and recognizing barriers to equal educational experiences for all children can lead to viable solutions related to the effects of incarceration on children (Turney & Haskins, 2014). While we did not find any relationship between coparents who can rely on one another and child outcomes, previous research has shown that children of an incarcerated parent are more likely to experience homelessness, housing instability, food insecurity, and lower rates of educational achievement (Sexton, 2016), thus displaying that this is a systemic problem (Tadros et al, 2021b).…”
Section: Discussioncontrasting
confidence: 96%
“…Despite providing couple and family community–based services, these service professionals seldomly work within adult criminal justice settings (Datchi et al, 2016; Tadros et al, 2020b). Traditionally, family services have not been provided in incarcerated facilities (Datchi & Sexton, 2013; Datchi et al, 2016; Tadros et al, 2020b, 2021; Tadros & Ogden, 2020). While reviewing the literature, only a few articles discussed family therapy in the incarcerated setting.…”
Section: Incarcerationmentioning
confidence: 99%
“…Through the inclusion of marriage and family programs in correctional settings, it would appear that there has been progress in improving marital and family satisfaction for incarcerated persons and families (Gendreau, 1996). Integrating families into treatment of incarcerated individuals may assist in enriching relationships as well as increasing the likelihood of successful reentry into the home and community (Tadros & Finney, 2018, Tadros et al, 2021). The literature displays that systemic models applied to the incarcerated population seem to be those adolescent-focused models and in juvenile settings (Dragomir & Tadros, 2020).…”
Section: Incarcerationmentioning
confidence: 99%
See 2 more Smart Citations